Preliminary survey of the nonvolant mammals of a remnant of coastal restinga habitat in eastern Sergipe, Brazil - Dias, Douglas de Matos; Mendonça, Luana Marina de Castro; Albuquerque, Natasha Moraes de; Terra, Rodrigo Farias de Carvalho; Silvestre, Saulo Meneses; Moura, Viviane Sodré; Beltrão, Raone; Ruiz-Esparza, Juan; Rocha, Patrício Adriano da; Ferrari, Stephen Francis (Natureza Online, 2017)
The present study reports on the diversity of nonvolant mammals in a remnant of coastal restin-ga habitat in eastern Sergipe, Brazil, the RPPN Caju, in the municipality of Itaporanga d’Ajuda. The spe-cies inventory was based on 24 Sherman-type traps, nine camera-traps, interviews with local residents, and the identification of vestiges such as feces and tracks. The study was conducted between the 21st and the 31st of October, 2014. We recorded 13 na-tive species, four of them were captured by Sher-man-type traps, two species of Didelphimorphia and other two of Rodentia. Other four species – Calli-thrix jacchus, Cerdocyon thous, Procyon cancrivo-rus and Dasyprocta sp. – were recorded by camera–traps. Vestiges of Puma yagouaroundi, Euphractus sexcinctus, Hydrochoerus hydrochaeris, Sylvilagus brasiliensis, and Tamandua tetradactyla were en-countered. Two domestic taxa (Canis lupus familia-ris and Felis catus) were also recorded, although not counted in species list. Most of the species recorded in this study are habitat generalists, with an ample geographic distribution in Brazil. The reduced spe-cies richness recorded in this study is typical of other sites in Sergipe, and may be related to a number of different factors, such as naturally low densities to a long history of habitat degradation in the study area. The RPPN Caju may nevertheless represent an important refuge for the local mammalian fauna, given its location within a region of considerable environmental fragility. The presence of domestic mammals represents an additional threat, and may be a major factor in population decline and local extinctions. The present inventory is preliminary, however, and further fieldwork will be required to confirm the local occurrence of less common species known to inhabit the region. Even so, this study re-presents an important contribution to the understan-ding of the distribution of nonvolant mammals in the coastal restinga systems of the Brazilian Northeast.